Applications of Pristine and Functionalized Carbon Nanotubes, Graphene, and Graphene Nanoribbons in Biomedicine - Maria G. Burdanova (MDPI AG, 2021)
This review is dedicated to a comprehensive description of the latest achievements in the chemical functionalization routes and applications of carbon nanomaterials (CNMs), such as carbon nanotubes, graphene, and graphene nanoribbons. The review starts from the description of noncovalent and covalent exohedral modification approaches, as well as an endohedral functionalization method. After that, the methods to improve the functionalities of CNMs are highlighted. These methods include the functionalization for improving the hydrophilicity, biocompatibility, blood circulation time and tumor accumulation, and the cellular uptake and selectivity. The main part of this review includes the description of the applications of functionalized CNMs in bioimaging, drug delivery, and biosensors. Then, the toxicity studies of CNMs are highlighted. Finally, the further directions of the development of the field are presented.